Monster needs a Christmas tree : a story - Czajak, Paul (Czajak, Paul. Monster & me book., 2014)
On the day before Christmas, Monster knows he needs a special tree but there are so many fun things to do, including having a snowball fight, sledding, and visiting Santa, that finding the perfect tree may take some creativity.